Legal Aspects of Informed Consent for Patients Requiring Emergency Treatment - Putri, Junia; Bihar, Syamsul; Jamaludin, Ahmad (Research Horizon, 2025)
In the medical field, doctors are required to have a permit before performing medical procedures. However, doctors often encounter patients in emergency situations who cannot give consent and are not accompanied by family. This study aims to examine the implementation of informed consent in Indonesia to identify challenges and possible solutions. Through a literature review, this study uses a normative legal approach. Therefore, Law Number 17 of 2023, Article 293(9) exempts doctors from the obligation to obtain medical consent in emergencies. The result shows According to Article 275 paragraphs (1) and (2), doctors are also legally protected from payment demands after providing first aid to save lives or prevent disability. Because they offer an agreement on efforts and are exempt from legal responsibility if the patient’s goal is to be helped, doctors should not hesitate to act quickly in emergencies. This study found that Law Number 17 of 2023 provides doctors with legal protection to act without consent in emergencies, thereby reducing the risk of legal liability. The conclusion is that clear guidelines and ongoing legal education for medical personnel are essential to ensure safe and legal emergency care.